2021
DOI: 10.1097/mcc.0000000000000858
|View full text |Cite
|
Sign up to set email alerts
|

How trustworthy guidelines can impact outcomes

Abstract: Purpose of reviewIf developed using rigorous methods and produced in a timely manner, clinical practice guidelines have the potential to improve patient outcomes. Although the COVID-19 pandemic has highlighted the challenges involved in generating reliable clinical guidance, it has also provided an opportunity to address these challenges. Recent findingsNew research addressing drugs for COVID-19 is being produced at unprecedented rates. Incorporating this new knowledge into patient care can be daunting for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…The majority of the studies reported living guideline activities conducted by the WHO (15, 71.4%),14 19 24–35 followed by China (4, 19%),36–39 Chile (1, 4.8%)40 and Lebanon (1, 4.8%) 41. All studies included in this review were published between 2019 and 2022.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the studies reported living guideline activities conducted by the WHO (15, 71.4%),14 19 24–35 followed by China (4, 19%),36–39 Chile (1, 4.8%)40 and Lebanon (1, 4.8%) 41. All studies included in this review were published between 2019 and 2022.…”
Section: Resultsmentioning
confidence: 99%
“…Synoptically, they attributed the favorable outcome to a profound lessening of type I interferon responses with a parallel decrease of pro-inflammatory IL-6/IL-10 ratios in tissues as well as promotion of M2 macrophage polarization [63]. Furthermore, more than 20 randomized controlled trials (RCT) [60] and eight meta-analyses [61,[64][65][66][67][68][69] have been conducted, with an overall reported conclusion being a major reduction of COVID-19 morbidity and mortality; such RCTs reported significant decreases in mortality accompanied by significant decreases in the length of viral clearance and clinical recovery. Several controlled prophylaxis trials showed a lower risk of contracting SARS-CoV-2 to be associated with regular usage of ivermectin [70].…”
Section: Covid-19 Evidence-based Treatmentsmentioning
confidence: 99%